`-> x^2 - 2x - 2 = x^2 + 18x - 40`
`<=> 38 = 20x`
`=> x = 19/10 = 1,9`
`-> x^2 - 2x - 2 = x^2 + 18x - 40`
`<=> 38 = 20x`
`=> x = 19/10 = 1,9`
Giải phương trình
a/ 2x - (x - 3)(5 - x) = (x+4)\(^2\)
b/ (4x + 1)(x - 2) + 25 = (2x+3)\(^2\) - 4x
Giải phương trình \(\frac{x^2-2x+2}{x-1}+\frac{x^2-8x+20}{x-4}=\frac{x^2-4x+6}{x-2}+\frac{x^2-6x+12}{x-3}\)
Giải phương trình \(\dfrac{1}{x^{2^{ }}+9x+20}+\dfrac{1}{x^{2^{ }}+11x+30}+\dfrac{1}{x^{2^{ }}+13x+42}=\dfrac{1}{18}\)
Giải phương trình:
a) (x + 5)(x + 2) = 3(4x - 3) + (x - 5)2
b) 12 - 2(1 - x)2 = 4(x - 2) - (x - 3)(2x - 5)
c) (x - 3)3 - 2(x - 1) = x(x - 2)2 - 5x2
d) x(x + 3)2 - 3x = (x + 2)3 + 1
Giải các phương trình
1, \(\dfrac{1}{x}-\dfrac{2}{x+1}=\dfrac{3}{x^2+x}\)
2, \(\dfrac{x+2}{x-2}-\dfrac{1}{x}=\dfrac{2}{x\left(x-2\right)}\)
3, \(\dfrac{x-2}{x+2}-\dfrac{3}{x-2}=\dfrac{2\left(x-11\right)}{x^2-4}\)
Bài 1: Giải các phương trình:
a) \(x+\frac{2x-2}{1-x}=-1\)
b) \(x+\frac{1}{x}=2\)
Bài 2: Giải các phương trình:
a) \(\frac{x}{x-2}=\frac{x-2}{x-3}\)
b) \(\frac{x+3}{x-1}-\frac{3}{x-1}+\frac{x^2-2}{1-x^2}=0\)
c) \(\frac{2x-4}{x-1}-\frac{x-3}{x-2}=1\)
Bài 3: Giải các phương trình:
a) \(\frac{2x}{x-1}-\frac{x}{x-2}=\frac{x^2}{\left(x-1\right)\left(x-2\right)}\)
b) \(\frac{1}{x+2}-\frac{6}{x-1}+\frac{8}{\left(x+2\right)\left(x-1\right)}=0\)
c) \(\frac{x+2}{x+3}-\frac{x+1}{x-1}=\frac{4}{\left(x+3\right)\left(x-1\right)}\)
Giải các phương trình
1,\(x\left(x-1\right)=2\left(x-1\right)\)
2, \(\left(x+2\right)\left(2x-3\right)=x^2-4\)
3, \(x^2+3x+2=0\)
4, \(5x^2+5x+3=0\)
5, \(x^3+x^2-12x=0\)
Giải các phương trình
1,\(3x-1=0\\\) 4, \(\dfrac{x}{3}-\dfrac{x}{5}=4\)
2, \(2-x=3x+1\) 5, \(\dfrac{x-1}{4}+\dfrac{2x+1}{6}=\dfrac{3}{2}\)
3, \(2\left(x-2\right)-1=5x\)
giải phương trình sau:
a. (x-1)3-x(x+1)2=5x(2-x)-11(x+2)
b. (x+1)(x2-x+1)-2x= x(x-1)(x+1)
c. (x-2)3+(3x-1)(3x+1)=(x+1)3